(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
This scientific article studies the national liberation struggle in Turkestan in 1916, in particular the events that took place in the Syrdarya region. The article analyzes the social, economic and political factors of this period, their impact on the national movements among the local population. It also highlights the strategies of the population of the region to resist the pressure of the Russian Empire, the historical significance of the main characters and events in the struggle. The article, analyzing various archival documents, personal memoirs and historical literature, assesses the role of the Syrdarya region in the liberation struggle and its place in the context of the broader national movement.